Assessing Patients' Satisfaction about Performance of Health Transformation Plan in Teaching Hospitals Affiliated to Southern Khorasan Province In 2016 - fariba asadi; seyyedeh sara afrazandeh; maryam ebrahimi (Tehran University of Medical Sciences, 2018)
Background: One of the hospitals' goals is providing high quality of health for patients and patient satisfaction is one of the indicators of quality of health care in hospitals in all countries. The present study aimed to evaluate patients' satisfaction about performance of health transformation plan in teaching hospitals affiliated to southern Khorasan province in 2016.   Materials and Methods: This study was a cross-sectional, descriptive-analytic one which 410 patients admitted to seven public hospitals of south Khorasan province were evaluated using a standard questionnaire on patient satisfaction during one month. Data analysis was performed by SPSS22 software using descriptive and inferential statistics.   Results: level of 51.5% patients 'satisfaction was assessed high, 37.1% in a good, 9.9% moderate and 1.6 low level. Regression analysis revealed that average score of satisfaction with education level and economic situation had a significant association (p <0.05) which patients with higher education level and better economic status had less satisfaction. There was no significant relationship between other demographic variables and satisfaction level.   Conclusion: According to study results, it can be concluded that the health transformation plan can achieve its goals and success regarding patients' satisfaction and patient costs reduction due to patientschr('39') perspective. In order to increase patients' satisfaction, paying more attention to welfare and nutrition and evaluating satisfaction in other groups (nurses, physicians and personnel) recommended.